2022
DOI: 10.3390/buildings12081140
|View full text |Cite
|
Sign up to set email alerts
|

Using RPA for Performance Monitoring of Dynamic SHM Applications

Abstract: Robotic Process Automation (RPA) is a source of growing applications in a number of industries both as an individual technology and as a complement to other technologies (such as Internet of Things (IoT)). RPA allows the automation of human activities on a computer, especially when these activities are repetitive and high in volume. RPA saves man-hours and increases the productive capacity of the processes. The application of RPA in civil engineering is still in its early stages, and there has been little work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Nonetheless, the eigenfrequency analysis of LARA has previously been validated through 11 experiments on an actuator in the structural laboratory of the Universitat Politècnica de Catalunya (UPC) university, Barcelona, Spain [47,71]. In that work, it was reported that eigenfrequency analysis of LARA had 0.5% and 0.003% for signals with 0.1 and 32 Hz, respectively.…”
Section: Post-synchronization Application Of Laramentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the eigenfrequency analysis of LARA has previously been validated through 11 experiments on an actuator in the structural laboratory of the Universitat Politècnica de Catalunya (UPC) university, Barcelona, Spain [47,71]. In that work, it was reported that eigenfrequency analysis of LARA had 0.5% and 0.003% for signals with 0.1 and 32 Hz, respectively.…”
Section: Post-synchronization Application Of Laramentioning
confidence: 99%
“…It should be noted that the physical construction of LARA is part of the open-design movement that can provide new opportunities for other researchers to produce their own sensors instead of purchasing expensive commercial solutions. In order to encourage researchers to use LARA, the instructions for its manual alignment of 5 MPU9250 are presented in [47,71,72]. LARA is an open hardware prototype that has customization advantages.…”
Section: Ismamentioning
confidence: 99%
“…Considering the above, it is that low-cost sensor solutions have emerged, in order to improve efficiency in data collection, increase the quality of measurements, improve the speed of information collection, and reduce implementation costs [ 43 , 44 ]. For this reason, the electronic industry with different devices has provided alternatives for the sensorization of industrial processes, such as Arduino, and Raspberry Pi, among others.…”
Section: Introductionmentioning
confidence: 99%
“…5 in Table 2-2) is the only developed system with a very high sampling frequency, which requires further studying since the sampling frequency of the developed accelerometer is equal to the sampling frequency of the used circuit (LSM9DS1). Furthermore, it should be noted a developed vibration acquisition system from a circuit requires further laboratory validation tests because depending on the used microcontroller, cable and connections quality, and the data acquisition system, the noise density, sampling frequency and accuracy may alter [74]. Furthermore, the shown noise density in Table 2-2 is not reported from the experimental tests of the researchers.…”
Section: Further Analysis Of Thismentioning
confidence: 99%
“…It should be noted that each system may be useful for a specific use. Among the presented microcontrollers, Arduino Due seems to have the highest clock speed, making it very interesting for further development of lowcost solutions with the need for high sampling frequency [74].…”
Section: Arduinomentioning
confidence: 99%